P3.008 Epidemiological Correlates of Chlamydia Pgp3 Antibody in a Prospective Cohort of Men and Women. (13th July 2013) - Horner, P; Dickson, N; Wills, G; Righarts, A; Vieira, S; Young, S; McClure, M
Abstract : Background: Epidemiological correlates of chlamydia (CT) antibody were investigated in a longitudinal cohort of just under 1000 men and women born in Dunedin, New Zealand in 1972/1973 at ages 26, 32 and 38. Methods: Subjects were questioned on sexual behaviour and sexually transmitted infections (STIs) at ages 21, 26, 32 and 38 (1993–2011), and sera collected at ages 26, 32 and 38 for CT antibody. All sera were assayed by Pgp3 ELISA, and the age 32 samples by MOMP peptide ELISA, and assayed blinded. Ethical approval was obtained. Results: Pgp3 antibody was strongly associated with history of CT, but not other STIs (p > 0.3). This association was much stronger for women (p = < 0.001, OR 8, 95% CI 4–16.1) than men (p = 0.07, OR 2.64, 95% CI 0.82–8). At age 26, 17.4% (72/411) of all the women were Pgp3 sero-positive, as were 56.8% (25/44) of those giving a history of CT infection. For both men and women at age 26, Pgp3 antibody correlates with age at first intercourse and the number of partners. More women who were seropositive at age 26 lost Pgp3 antibody between the ages of 26 and 32 (25/67, 37.3%), than did seropositive women between 32 and 38 (7/56, 12.5%) (p = 0.003). At age 32 women with previous CT infection were more likely to have Pgp3 antibody (23/52, 44.2%) than MOMP antibody (12/52, 23.1%). Conclusion: Pgp3 antibody in women is strongly associated with past diagnosed CT infection, and at age 32 a more sensitive measure than MOMP antibody. It is associated with earlier age of first sexual intercourse and increasing number of partners, but not with a past history of other STIs. Pgp3 antibody prevalence declined over time. These data provide further information to show that Pgp3 antibody provides a measure of past CT infection.